The Reconstruction of The Role of Islam in Indonesia as A Propethic Religion - Naupal Naupal (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
After the end of Soeharto’s regime, in 52 districts produced 78 regulations (perda) influenced by sharia to purify Islam from secular institutions. Because of that, Islam in Indonesia now is criticized as having a tendency to be close to status quo, and resulting so many problems, such as being injustice and dehumanize. Islam as a prophetic religion, as a religion not only for faith to Allah, is also a religion that liberating people from violence and injustice, as Prophet Muhammad brought it. This academic writing , using the hermeneuticmethod fromPaul Ricoeur, analizes the situation, by proposing three ways outthrough the theory of critical ideology, and the deconstruction, and offering to accept plurality, to overcome the problems of complicated situation. Propethic religion might be the proper solution for the problems of Islam in Indonesia than priestly/institutional religion, in order to acheive the better Indonesian society, by practising tolerance, openess in mind, egaliter and democatic.